2017
DOI: 10.1063/1.5001724
|View full text |Cite
|
Sign up to set email alerts
|

Study on stress-wave propagation and residual stress distribution of Ti-17 titanium alloy by laser shock peening

Abstract: Laser shock peening has advantages of less restriction, better reinforcement, stronger controllability, and so on, which could greatly improve the fatigue properties of the material compared with traditional processes. In this paper, dual phase titanium alloy Ti-17 has been studied, and numerical simulation has been taken to analyze the stress-wave propagation rules in Ti-17 titanium alloy plates with different thicknesses. In addition, the distribution of residual stress which is obtained by experiments is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has been reported that the structure of the honeycomb is highly dependent on various factors such as solvent type, polymer side-chain length and the polymer concentration [49] . The SEM topography has been used as a powerful tool to detect both the size and shape of particles [ 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the structure of the honeycomb is highly dependent on various factors such as solvent type, polymer side-chain length and the polymer concentration [49] . The SEM topography has been used as a powerful tool to detect both the size and shape of particles [ 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%